2008
DOI: 10.1123/ijspp.3.4.424
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Wearing Lower-Body Compression Garments During Endurance Cycling

Abstract: Purpose:The present investigation examined the physiological and performance effects of lower-body compression garments (LBCG) during a one-hour cycling time-trial in well-trained cyclists.Methods:Twelve well-trained male cyclists ([mean ± SD] age: 20.5 ± 3.6 years; height: 177.5 ± 4.9 cm; body mass: 70.5 ± 7.5 kg; VO2max: 55.2 ± 6.8 mL·kg−1·min−1) volunteered for the study. Each subject completed two randomly ordered stepwise incremental tests and two randomly ordered one-hour time trials (1HTT) wearing eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
94
4
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(116 citation statements)
references
References 30 publications
13
94
4
5
Order By: Relevance
“…Such garments are commonly worn during exercise and in recovery by team sport athletes, and especially in individual sport athletes such as triathletes, cyclists and runners (Sperlich et al 2010). Some studies have reported that compression garments improve running economy (Bringard et al 2006b), reduce muscle oscillation (Doan et al 2003), lower blood lactate levels (Berry and McMurray, 1987) and enhance muscle oxygenation (Bringard et al 2006a;Scanlan et al 2008). However, only a limited number of studies have critically examined their effect on endurance running performance in controlled settings despite their widely accepted use.…”
Section: Introductionmentioning
confidence: 96%
“…Such garments are commonly worn during exercise and in recovery by team sport athletes, and especially in individual sport athletes such as triathletes, cyclists and runners (Sperlich et al 2010). Some studies have reported that compression garments improve running economy (Bringard et al 2006b), reduce muscle oscillation (Doan et al 2003), lower blood lactate levels (Berry and McMurray, 1987) and enhance muscle oxygenation (Bringard et al 2006a;Scanlan et al 2008). However, only a limited number of studies have critically examined their effect on endurance running performance in controlled settings despite their widely accepted use.…”
Section: Introductionmentioning
confidence: 96%
“…These show conflicting results. [4][5][6][7][8][9][10][11][12][13][14] Three recent studies demonstrated the effect of wearing GCS during running in trained male runners. [4][5][6] In 2 of these studies, 4,5 the effect of wearing GCS on heart rate was measured; the hypothesis was that an increase in venous return results in an increase in cardiac output and a decrease in heart rate.…”
mentioning
confidence: 99%
“…[2][3][4][5] In endurance racings, only one study 3 showed a discreet effect of CS (18-20 mmHg) after running on the treadmill, the running time and lactate levels. All other studies [6][7][8][9] did not show a conclusive difference (cycling, running and netball). A compression garment on the upper body 10 also did not show improved performance among kayakers.…”
Section: Clinical Studies Of Sports Performancementioning
confidence: 99%